FACILITATED TUCKING EFFECTIVE TO PAIN RELIEF ON THE PRETERM INFANTS IN PERINATAL UNIT IN JAKARTA - Eva Oktaviani; Yeni Rustina; Defi Efendi (Jurnal Keperawatan Indonesia, 2018)
Most preterm infants often need to be hospitalized more than one week in intensive care, so they undergo numerous repeated painful procedures such as blood collection. The study aimed to identify the effect of facilitated tucking for pain respond that is physiological parameter and duration of crying in preterm infants during blood collection. The study design was quasi experimental with nonequivalent control group pretest-posttest design. Fourty babies were divided into two groups; the intervention group (n= 20) who received facilitated tucking during blood collection and the control group (n= 20) without facilitated tucking, with consecutive sampling technique. Statistical analyses used were General Linear Model+post hoc, Mann-Whitney, and Independent T-Test. There were significant means the difference in the heart rate, oxygen saturation, and duration of crying infants between non-intervention and intervention group. Duration of crying infants in intervention is shorter than the control group. Facilitated tucking is effective in pain reduction and crying time during blood collection. This finding implies a part of developmental care and should be attention for promoting pain management infants.